THE CONCEPT OF FATTY LIVER DISEASE ASSOCIATED WITH METABOLIC SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Fatty hepatosis is the most common chronic liver disease. According to statistics, non–alcoholic fatty liver disease is found in 6.3-33% of adults worldwide. In obese patients, this figure is even higher: it reaches 62-93%. The peak incidence in both men and women occurs at the age of 40-50 years. The mechanism of development of fatty hepatosis is quite complex and includes environmental factors (nutrition and physical activity of a person), hormonal background, genetic prerequisites. Normally, lipids should be transformed in the liver into other substances necessary for the proper functioning of the digestive system. But instead, they penetrate into the hepatocytes and accumulate there. The liver tissue in the areas of fatty infiltration becomes dense and can no longer perform its tasks. Steatosis develops - the initial stage of non-alcoholic fatty liver disease.